Integrated IoT System for Remote Health Monitoring in Home Hospitalization - Gramajo, Sergio; Torres, Carlos; Nuñez, Salvador; Scappini, Reinaldo; Roa, Jorge; Montiel, Raul (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2025)
The COVID-19 pandemic underscored the critical need for scalable and scientifically validated remote health monitoring systems. This work presents the development of an IoT system designed to monitor physiological and environmental parameters in home-hospitalized patients. The architecture comprises two complementary prototypes: (1) a wearable device capturing cutaneous temperature, single-lead ECG, pulse oximetry (SpO₂), non-invasive blood pressure monitoring, and fall detection; and (2) an environmental sensor unit recording atmospheric pressure, ambient temperature, light intensity, relative humidity, and CO₂ levels. Data is transmitted via hybrid WiFi/LoRaWAN connectivity to a cloud-based server utilizing optimized MQTT/CoAP protocols, where data science, through machine learning algorithms, generates real-time clinical alerts. Preliminary results demonstrate successful validation of the system architecture, rigorous medical sensor selection (AD8232, MAX30102), and proof-of-concept deployment. The solution shows significant potential to reduce the burden on hospital resources and enhance emergency response effectiveness in home-based care scenarios.